2004
DOI: 10.2193/0091-7648(2004)32[22:wapgdw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Weather and prairie grouse: dealing with effects beyond our control

Abstract: We used multiple‐linear‐regression methods to simultaneously assess effects of vegetative disturbance and weather on the production of sharp‐tailed grouse (Tympanuchus phasianellus) on Valentine National Wildlife Refuge (NWR) in Nebraska using a long‐term data set of harvest‐age ratios as production indices. After developing the model, we plotted the model‐averaged predictions of sharp‐tailed grouse production indices for Valentine NWR against actual sharp‐tailed grouse production indices for our reference are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
(27 reference statements)
0
37
0
Order By: Relevance
“…Brood success and chick survival remained low during both years in shrubsteppe, suggesting that within this cover type these reproductive parameters may have been affected by the moderate as well as the severe drought more than in mine reclamation. In north-central Nebraska, May average temperature, June average temperature, and cumulative precipitation from 1 January to 31 July were positively correlated with sharp-tailed grouse production, while June number of heat stress days and June number of days with precipitation over 2.54 mm were negatively correlated with production (Flanders-Wanner et al 2004). …”
Section: Climatic Factors/global Climate Changementioning
confidence: 97%
See 4 more Smart Citations
“…Brood success and chick survival remained low during both years in shrubsteppe, suggesting that within this cover type these reproductive parameters may have been affected by the moderate as well as the severe drought more than in mine reclamation. In north-central Nebraska, May average temperature, June average temperature, and cumulative precipitation from 1 January to 31 July were positively correlated with sharp-tailed grouse production, while June number of heat stress days and June number of days with precipitation over 2.54 mm were negatively correlated with production (Flanders-Wanner et al 2004). …”
Section: Climatic Factors/global Climate Changementioning
confidence: 97%
“…In north-central Nebraska, Flanders-Wanner (2004) found that May average temperature, June average temperature, and cumulative precipitation from 1 January to 31 July (drought index) were positively correlated with plains sharp-tailed grouse production (juveniles per adult in the fall harvest); conversely, June number of heat stress days and June number of days of precipitation greater than 2.54 mm were negatively correlated with production. The most valuable predictor of productivity was the drought index, although the relationship was not straightforward.…”
Section: Population Regulationmentioning
confidence: 98%
See 3 more Smart Citations